Relasi Gender Dalam Film-Film Bertema Islam - Ariza Qurrata A’yun (CandraRupa : Journal of Art, Design, and Media, 2019)
This study tries to discuss about gender relations are shown by both of movies by Hanung Bramantyo, which has different time setting and background. The film "Perempuan Berkalung Sorban" by setting of time in the 1990s situation whosebackground life in traditional boarding school in East Java. And the movie has titled "Hijab" by setting time in 2014 situation whose background life in Jakarta. Gender relation is the relationship between the main character, her good father, her husband, or her brother, in her attempt to raise the rights of women from the men who always positioned in the superior and detrimental to women. The problem is trying to answer is how the description of female main character in relation to the male character in their life in an Islamic films? The purpose of this study was to determine and describe of Muslim female main character in relation to the male figure in the Islamic films.In this study, the method performed is textual analysis Barthes semiotic property of the view denotation, connotation, and the myth of a text (dialogue or scene) in Islam films. The findings of the data in the form of denotation and connotation meaning every movie scene relating to gender relations in the film. -Perempuan Berkalung Sorban and Hijab-. It does not much have changed regarding the position of women in the film, even if displayed in Islamic films. True Islamic religion brought evolutionary teachings of liberation against the oppression of women by men; it is not reflected in either the Islamic movie. In the second story of the film is raised in this study there are texts or scenes that show the imbalance in gender relations.